Peroxisome proliferator‐activated receptor‐γ coactivator‐1α mediates neuroprotection against excitotoxic brain injury in transgenic mice: role of mitochondria and X‐linked inhibitor of apoptosis protein. (11th February 2016) - Mäkelä, Johanna; Mudò, Giuseppa; Pham, Dan Duc; Di Liberto, Valentina; Eriksson, Ove; Louhivuori, Lauri; Bruelle, Céline; Soliymani, Rabah; Baumann, Marc; Korhonen, Laura; Lalowski, Maciej; Belluardo, Natale; et al.
Abstract: Peroxisome proliferator‐activated receptor gamma coactivator‐1α (PGC‐1α) is a transcriptional coactivator involved in the regulation of mitochondrial biogenesis and cell defense. The functions of PGC‐1α in physiology of brain mitochondria are, however, not fully understood. To address this we have studied wild‐type and transgenic mice with a two‐fold overexpression of PGC‐1α in brain neurons. Data showed that the relative number and basal respiration of brain mitochondria were increased in PGC‐1α transgenic mice compared with wild‐type mitochondria. These changes occurred concomitantly with altered levels of proteins involved in oxidative phosphorylation (OXPHOS) as studied by proteomic analyses and immunoblottings. Cultured hippocampal neurons from PGC‐1α transgenic mice were more resistant to cell degeneration induced by the glutamate receptor agonist kainic acid. In vivo kainic acid induced excitotoxic cell death in the hippocampus at 48 h in wild‐type mice but significantly less so in PGC‐1α transgenic mice. However, at later time points cell degeneration was also evident in the transgenic mouse hippocampus, indicating that PGC‐1α overexpression can induce a delay in cell death. Immunoblotting showed that X‐linked inhibitor of apoptosis protein (XIAP) was increased in PGC‐1α transgenic hippocampus with no significant changes in Bcl‐2 or Bcl‐X. Collectively, these results show that PGC‐1α overexpression contributes to enhanced neuronal viability by stimulating mitochondria number and respiration and increasing levels of OXPHOS proteins and the anti‐apoptotic protein XIAP. Abstract : PGC‐1α is a transcriptional coactivator regulating mitochondrial biogenesis and cell defense. Overexpressing PGC‐1α in transgenic mice protected hippocampal neurons against excitotoxic damage induced by kainic acid. Increased neuronal resilience afforded by PGC‐1α was associated with an enhanced mitochondrial respiration and the expression of specific proteins as revealed by proteomics. The modulation of PGC‐1α regulated signaling pathways may constitute promising targets for neuroprotection in various human neurodegenerative diseases.